IMPLEMENTASI PENGGUNAAN MICROSOFT EXCEL VBA UNTUK MEMBUAT LAPORAN KEUANGAN SEDERHANA UMKM XYZ STUDIO - Axshelby, Olivya Balqis; Sharasanti, Diah Anugrah (ITB AAS INDONESIA, 2024)
Financial recording is a significant point for small to multinational companies. Financial recording provides information about the company’s condition that later will be used as the basis of decision making for the company. Microsoft Excel is a beneficial program for financial recording. This program is quite simple to use, can be adjusted with user’s preferences, and easy to obtain. In Microsoft Excel there is a Macro Visual Basic feature. This feature helps users to automate required action, so that users could work effectively and efficiently. Considering the importance of financial recording for decision making, the author wrote this final report that discusses “Simple Financial Recording Using Microsoft Excel VBA for UMKM XYZ Studio”. UMKM XYZ Studio is a manufacturing company for women’s syar’i clothes that is located in South Tangerang. For the purpose of data collection, the Author used some techniques which are questionnaire, literature studies, and documentation. Result of data collection and the process of creating a simple financial recording application using Microsoft Excel VBA are explained in this report.